Finance and Development, September 2004. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2004)
This paper highlights that for the IMF, July 2004 marked the 60th anniversary of the conference in Bretton Woods, New Hampshire, when delegations from 44 allied countries drafted and agreed upon the IMF's charter. The IMF's role and work have evolved in response, but like any large organization, its ability to change has been limited by its own rules and mandate and has been held back by inertia. This year's anniversary offers an opportunity to reflect on how gaps between the reality and the ideal might be closed in the coming years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet